2009
DOI: 10.1118/1.3056464
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the x‐ray tube anodes’ surface profile and its effects on the x‐ray spectra

Abstract: An experimental study--involving measurements with an optical microscope, a profilometer, and a scanning electron microscope--for determination of the surface profile of x-ray tube anodes is presented. The islands on the "mud-flatting" surface are separated by approximately 8 microm deep cracks. The surface roughness on the island is typically below 1 microm, and the area ratio of cracks to the total surface is higher on the more extensively used regions (anode aging). A simple model was proposed to calculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
1
13
0
1
Order By: Relevance
“…Our results are in good agreement with the work of Erdelyi et al 34 where a 5% intensity loss for anode angle of 6°a nd tube voltage of 100 kVp was reported for an 8 m mean depth of the cracks. The difference ͑1% increase͒ is likely due to the empirical approach followed by the authors as well as the assumption that electrons strike the anode surface at normal incidence and that the associated x rays do not scatter in the anode block.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in good agreement with the work of Erdelyi et al 34 where a 5% intensity loss for anode angle of 6°a nd tube voltage of 100 kVp was reported for an 8 m mean depth of the cracks. The difference ͑1% increase͒ is likely due to the empirical approach followed by the authors as well as the assumption that electrons strike the anode surface at normal incidence and that the associated x rays do not scatter in the anode block.…”
Section: Discussionsupporting
confidence: 93%
“…32 The same group reported that anodes with a surface roughness of about 1.4-3.8 m correspond to additional filtration by tungsten with a thickness of 2.12-8.21 m. 33 Other investigators presented detailed measurements of anode surface profiles of 19 diagnostic x-ray tubes and predicted empirically an intensity loss of 4% for rough anodes with 8 m deep cracks. 34 Although Monte Carlo simulation has experienced considerable growth both in terms of number of articles and diversity of studies, 35 to the best of the authors' knowledge, this is the first attempt to address the issue of anode roughening as a factor influencing x-ray spectra through MC modeling. The limited applicability of analytical models for treating anode roughness on one hand and our previous experience with MCNP 36,37 on the other hand motivated us to carry out this work through MC-based simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous experimental results have shown that the surface roughness is cylindrically symmetric around the surface normal. 13 In other words, the surface roughness on the anode surface is isotropic. The measured angular dependency of the detected intensity values also confirms the cylindrical symmetry of the x-ray beam.…”
Section: Iia Mcnpx Input Geometry and Parametrizationmentioning
confidence: 99%
“…These typical parameters were obtained from an experimental study and were determined by an optical microscope, a profilometer, and a scanning electron microscope. 13 The intensity of the emitted x-ray was analyzed. However, the angular analysis of the HVL value uses air kerma values, since the standard measurements use this quantity.…”
Section: Iib Applied Surface Profilesmentioning
confidence: 99%
“…Ebben a fejezetben ismertetem a Maxiray 150 típusú röntgencsövek anódjain végzett vizsgálataink eredményeit, amely egy referált folyóiratcikkben jelent meg [31]. Az anódok különböző technikákkal lettek megvizsgálva, ideértve az optikai mikroszkópot, a profilométert és a pásztázó elektronmikroszkópot.…”
Section: Maxiray 150 Típusú Röntgencsövek Anódjainak Vizsgálataunclassified